Entrepreneurship and Equilibrium - Tang, Ying (2021)
Neoclassic economic theory regards equilibrium, whether general or partial, as a crucially important foundation of the dismal science[1]. In the view of mainstream economists, the general equilibrium framework not only an investigation of the economy in terms of its perfect qualities, but also is suitable as an end or goal of action. The Austrian school, in contrast, sees equilibrium (or the evenly rotating economy - ERE) merely as a tendency for economic activities to move us in that direction, but it is never attained. Praxeological economics has thus concentrated not on equilibrium, but on the process by which the market moves toward it. Since the process of shifting resources to meet these ends cannot be achieved spontaneously, entrepreneurship plays a key role. In Mises and Rothbard’s view, entrepreneurship involves uncertainty bearing which beyond the alertness emphasized by Hayek and Kirzner; on the other hand, unlike Lachmann looks the economy as a kaleidoscope and rejects the ERE, Mises and Rothbard regard the ERE as an indispensable way to understand the economy.   [1] As Frank H. Hahn said “Whatever economics is used or thought about, equilibrium is a central organizing concept.” (Hahn 1984: 43). Many economists and philosophers of science consider mathematical neoclassical general equilibrium theory as one of the peak achievements of economics (Rosenberg, 1992). Tieben (2012) stated that policy-makers and theorists of all schools of economics all use some form of equilibrium theory to develop their ideas and support their main theoretical and political claims. Lawson (2005) indicated that the equilibrium concept is a major cause of controversy between different schools of economic thought. A.W. Bob Coats even deems it the case that “economics has been dominated throughout its history by a single paradigm – the theory of economic equilibrium via the market mechanism.” (Coats 1969: 292).